Incentive mechanisms to prevent efficiency loss of non-profit utilities - Barreto, Carlos; Mojica-Nava, Eduardo; Quijano, Nicanor (International journal of electrical power & energy systems, 2019)
•We investigate how demand response affects the efficiency of non-profit utilities.•We show that, without proper coordination, users can consume twice the optimal demand.•We prove that non-profit utilities can have an arbitrarily large efficiency loss.•We mitigate the efficiency losses with a mechanism that preserves the user's privacy.•We show two instances of incentives that satisfy either deficit or surplus in budget. The modernization of the power system introduces technologies that may improve the system’s efficiency by enhancing the capabilities of users. Despite their potential benefits, such technologies can have a negative impact. This subject has widely analyzed, mostly considering for-profit electric utilities. However, the literature has a gap regarding the impact of new technologies on non-profit utilities. In this work, we quantify the price of anarchy of non-profit utilities, that is, the cost caused by lack of coordination of users. We find that users, in the worst case, can consume up to twice the optimal demand, obtaining a small fraction of the optimal surplus. For this reason, we leverage the theory of mechanism design to design an incentive scheme that reduces the inefficiencies of the system, which preserves the privacy of users. We illustrate with simulations the efficiency loss of the system and show two instances of incentive mechanism that satisfy either budget balance and budget deficit.